Moralities of Muslim and the Advancement of Western World in the Perspective of Suluk Linglung - zarkasi, fatchullah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This research aims to discuss about Muslims' moralities upon the Western World's advancement in the teachings of the Islamic holy book whose the first revelation that came down was the command to read, understand and develop. Muslims must have the courage to acknowledge the advancement, including that of Western countries with all their civilizational progress, even though it is also influenced by ideology, state, and religion; which is also in line with the values contained in the work of Suluk Linglung by Sunan Kalijaga, one of Muslim saints in medieval Indonesia. By using the Gadamer’s hermeneutic method, the author tried to observe, understand, confirm, and look for similarities between the values of Suluk Linglung and the progressive civilization already exists in Western society. The author argues that Muslims must avoid and discard negative values from Western society's culture as they do not exist in Suluk Linglung Sunan Kalijaga.